2013
DOI: 10.1002/j.0022-0337.2013.77.8.tb05570.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology Education in North American Dental Schools: The Basic Science Survey Series

Abstract: As part of the Basic Science Survey Series (BSSS) for Dentistry, members of the American Dental Education Association (ADEA) Physiology, Pharmacology, and Therapeutics Section surveyed course directors of basic pharmacology courses in North American dental schools. The survey was designed to assess, among other things, faculty afiliation and experience of course directors, teaching methods, general course content and emphasis, extent of interdisciplinary (shared) instruction, and impact of recent curricular ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…A possible explanation is that over 72 % of respondents in the current study graduated from the Canadian Memorial Chiropractic College where students presently receive 30 h of training in pharmacology and toxicology [ 25 ]. Although this number of hours in pharmacology education is above the World Health Organization standards for chiropractic, students in other healthcare professions such as dentistry complete an average of almost 70 h [ 26 ] and chiropractic students in Switzerland take over 80 h in pharmacology at the University of Zürich (C.K. Peterson, personal communication, 18 January 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that over 72 % of respondents in the current study graduated from the Canadian Memorial Chiropractic College where students presently receive 30 h of training in pharmacology and toxicology [ 25 ]. Although this number of hours in pharmacology education is above the World Health Organization standards for chiropractic, students in other healthcare professions such as dentistry complete an average of almost 70 h [ 26 ] and chiropractic students in Switzerland take over 80 h in pharmacology at the University of Zürich (C.K. Peterson, personal communication, 18 January 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is widely established that the implementation of active-teaching modalities increases students' satisfaction, most foundational courses such as pharmacology remain lecture-based. 7,24,25 The development of such active-teaching sessions is a timeconsuming task not easily achieved by faculty members who have many other important clinical and/or research responsibilities and clinical activities generally take priority over faculty member teaching obligations. 26 Investing significant resources to hire a professional pharmacology educator allows a school to bypass this challenge and further justify the investment.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] One strategy in these curricular modifications is to emphasize the importance of pharmacology as an integrative science. [5][6][7][8]11 Schools have shifted away from teaching pharmacology, physiology, and therapeutics in silos and toward teaching interdisciplinary curricula that emphasizes the interrelatedness of basic and clinical principles. One study reported high student satisfaction when an interdisciplinary approach was used to teach pharmacology topics in combination with physiology topics in the neurosciences.…”
Section: Introductionmentioning
confidence: 99%
“…The survey was designed to assess the effect of recent curricular changes between system-based learning and others. Course directors reported that curricular changes affect their pharmacology lecturers [13].…”
Section: Discussionmentioning
confidence: 99%